Características de durabilidade de concretos com cinza volante e cinza de casca de arroz com e sem beneficiamento - Cezar, Daiana de Souza (2011)
The construction industry has been studying the possibility of using industrial subproducts, as a strategy to remedy the environmental matters, considering that the sub-products are generated in large quantities and mostly without specific destination. In the present study investigates the feasibility of using the RHA residual, natural or ground, in structural concrete, in partial replacement of Portland cement, from the analysis of durability characteristics of the concrete. However, some natural rice husk ash have natural expansive effect due to the reaction of silica under form of microcrystalline and the cement alkali. Thus, it justifies the use of fly ash, forming ternary mixtures, as the solution to mitigate the expansion generated by alkaliaggregate reaction (AAR) or alkali-silica (RAS). For this, three binders mixtures were tested: one composed with the RHA natural + FA, one with RHA ground + FA and the last one composed with a reference mixture 80% of Portland cement and 20% of FA, in which confronted the results. It was adopted the replacement levels of 15% of RHA, and the relations a/g of 0.45; 0.55 and 0.65. It was conducted the trials of apparent electrical resistivity, specific electrical conductivity, resistance to chloride penetration according to the method of accelerated penetration ASTM C1202 (EAPC). Additionally, the trials of axial compressive strength and water absorption by capillarity were performed, according to requirements of ABNT. The obtained results in the research confirm that is feasible to use the residual RHA, natural or ground, as partial replacement of Portland cement, in concrete for structural use. It was found that the age and the ratio a/g showed a significant influence on the electrical resistivity and electrical conductivity of concrete, mainly due to changes in pore structure and the quantity and composition of them solution, showing there is a great correlation among these factors. As for the axial compressive strength, at 182 days, the mixture composed with RHA ground presented higher performance than to the reference mixture. However, for the mixing with RHA natural, the same course was not observed. In the EAPC the use of RHA ground, burned without temperature control, resulted in lower values of loads bystanders and lowest penetration depths, when compared to the mixtures with RHA natural and of reference. In the case of water absorption by capillarity, it was found that the use of RHA, in general, decreased the water absorption of concrete.